What's in an index? Comparing the ecological information provided by two indices to assess the status of coralligenous reefs in the NW Mediterranean Sea. Issue 6 (19th May 2017) - Piazzi, Luigi; Bianchi, Carlo Nike; Cecchi, Enrico; Gatti, Giulia; Guala, Ivan; Morri, Carla; Sartoretto, Stéphane; Serena, Fabrizio; Montefalcone, Monica
Abstract: This study compared the results obtained through the concurrent use of the two indices ESCA (Ecological Status of Coralligenous Assemblages) and COARSE (COralligenous Assessment by ReefScape Estimate) to define the ecological status of coralligenous reefs. The study evaluated: i) the effectiveness of the two indices at a regional spatial scale (100 s of km); ii) the descriptors that mostly influence the indices; and iii) the ecological information provided by the two indices. Both ESCA and COARSE were applied to coralligenous reefs selected at sites affected by different human‐induced pressures. The two indices provided different but complementary information to determine the intrinsic quality of coralligenous reefs and to detect the effects of human pressures on the associated assemblages. The simultaneous use of ESCA and COARSE can be effective in providing information about the alteration of ecological quality of coralligenous reefs, in order to achieve the requirements of European directives.